2014
DOI: 10.1161/circgenetics.113.000332
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Linkage and Regional Association Study of Blood Pressure Response to the Cold Pressor Test in Han Chinese

Abstract: Background Blood pressure (BP) response to cold pressor test (CPT) is associated with increased risk of cardiovascular disease. We performed a genome-wide linkage scan and regional association analysis to identify genetic determinants of BP response to CPT. Methods and Results A total of 1,961 Chinese participants completed the CPT. Multipoint quantitative trait linkage analysis was performed, followed by single-marker and gene-based analyses of variants in promising linkage regions (logarithm of odds, LOD ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…TMC2 is a potential ion channel required for the mechano-transduction of cochlear hair cells [42]. A study in the Han Chinese population reported that TMC2 was among the top genes associated with BP response to the cold pressor test (CPT), which is associated with an increased risk of cardiovascular disease [43].…”
Section: Discussionmentioning
confidence: 99%
“…TMC2 is a potential ion channel required for the mechano-transduction of cochlear hair cells [42]. A study in the Han Chinese population reported that TMC2 was among the top genes associated with BP response to the cold pressor test (CPT), which is associated with an increased risk of cardiovascular disease [43].…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence identifying products of the serine/threonine kinase 35 ( STK35 ) gene as suitable targets for diagnosis or intervention in cardiac pathologies ( Lamore et al, 2017 ; Yang et al, 2014 ), colorectal and other cancers ( Capra et al, 2006 ) and malaria ( Prudêncio et al, 2008 ), hence investigations of its physiological roles are of great interest. STK35 was originally identified as a binding partner of the PDZ-LIM protein, CLP-36, and named Clik1, for CLP-36 interacting kinase 1.…”
Section: Introductionmentioning
confidence: 99%
“…A genome-wide linkage study followed by single nucleotide polymorphism screen of linked regions identified variants in the MCM8, SLC23A2 and STK35 genes associated with the blood pressure response to the cold pressor test, via unknown pathways. (90)…”
Section: Autonomic Tone: Definition Measurement Heritability and Umentioning
confidence: 99%